Association of political candidates and ulamas during the 2019 election on Twitter - Devi Tri indriasari; Karman (Jurnal Studi Komunikasi, 2023)
This article explores how Indonesian political actors associate themselves with Ulamas through Twitter visual messages to symbolise Islamic piety during the Indonesian Presidential Election 2019. Despite past political events, socio-political dynamics are still relevant to understanding the current political climate. This article employed a qualitative approach by observing and analysing messages from @jokowi, the official account of the elected President, during the political contestation period. Specifically, multimodal analysis was used to examine visual data. We conclude that Islamic piety symbolisms were strategically used as a political instrument during the Election. Political actors, such as Jokowi, associated themselves with Islamic piety symbols and other Islamic cultural attributes to construct a certain strong image and appeal to the Indonesian Muslim voters. An association with Islamic piety symbols could boost his image and appeal to voters.